Background removal in scanning tunneling spectroscopy of single atoms and molecules on metal surfaces - Wahl, Peter; Diekhöner, Lars; Schneider, M. Alexander; Kern, Klaus (Review of Scientific Instruments, 2008)
Scanning tunneling spectroscopy has developed into a powerful spectroscopic technique that has found wide application in the atomic scale characterization of the electronic properties of clean surfaces as well as adsorbates and defects at surfaces. However, it still lacks the standard methods for data treatment and removal of artifacts in spectra as they are, e.g., common in photoemission spectroscopy. The properties of the atomic scale tip apex-the probe of the instrument-tend to introduce spurious background signals into tunneling spectra. We present and discuss two methods which permit to extract tip-independent information from low temperature tunneling spectra acquired on single atoms and molecules on single crystal surfaces by background subtraction. The methods rely on a characterization of the tip on the clean metal surface. The performance of both methods is demonstrated and compared for simulated and experimental tunneling spectra. (C) 2008 American Institute of Physics.